2016
DOI: 10.18632/oncotarget.9238
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox protein VentX induces p53-independent apoptosis in cancer cells

Abstract: Identifying novel tumor suppressors holds promise for improving cancer treatment. Our recent studies identified VentX, a homeobox transcriptional factor, as a putative tumor suppressor. Here we demonstrate that VentX exerts strong inhibitory effects on the proliferation and survival of cancer cells, but not primary transformed cells, such as 293T cells. Mechanistically, both in vitro and in vivo data showed that VentX induces apoptosis of cancer cells in a p53-independent manner. We found that VentX expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Apoptotic activity can be reflected by the ratio of Bcl-2/Bax (24). The nuclear enzyme poly(ADP-ribose) polymerase (PARP) is a key modulator of the apoptotic pathway, which can be proteolytically cleaved by caspase-3/7 when cell apoptosis occurs (35). In the present study, C646 treatment decreased the ratio of Bcl-2/Bax in the 5 GC cell lines.…”
Section: Discussionmentioning
confidence: 50%
“…Apoptotic activity can be reflected by the ratio of Bcl-2/Bax (24). The nuclear enzyme poly(ADP-ribose) polymerase (PARP) is a key modulator of the apoptotic pathway, which can be proteolytically cleaved by caspase-3/7 when cell apoptosis occurs (35). In the present study, C646 treatment decreased the ratio of Bcl-2/Bax in the 5 GC cell lines.…”
Section: Discussionmentioning
confidence: 50%
“…It is the first report of aberrant expression of VENTX, as a member of BMP signaling as well as a homeobox gene, in ESCC and its correlation with SALL4 as a stemness marker. VENTX is introduced as a tumor suppressor gene in colon and lung cancers . Through the progression of stages of the tumors, tumor invasion and tumor cell metastasis to the lymph nodes in ESCC, the expression of VENTX was significantly correlated with SALL4 , which suggests an oncogenic role for VENTX in ESCC progression and metastasis through correlation with stemness state regulator SALL4 .…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, whether these factors can be targeted to turn TAMs into a tumoricidal cells remains unclear. As a unique human hematopoietic transcriptional factor that does not have a murine homolog, VentX was found to have essential role in controlling proliferation and differentiation of hematopoietic cells and function as a p53-independent tumor suppressor 12 , 15 , 16 , 38 40 . Data of our current study suggested VentX controls TAM plasticity, which in turn, reverts immune suppression at the TME through regulating TIL differentiation and function, which was supported by both in vitro and in vivo studies (Figs.…”
Section: Discussionmentioning
confidence: 99%